BLOOD CULTURE FOR SEPSIS DETECTION - Ms Sriparna Acharyya; Dr Meena K. Krishnan; Mr Avadhesh Kumar Yadav; Ms Subarna Chakraborty; Ms Jaya Chatterjee; Mr Vineeth P; Mr Rajendra Sahu (Galaxy International Interdisciplinary Research Journal, 2022)
Collection and inoculation of blood into the culture medium to grow pathogenic microorganisms for diagnosis of sepsis. Blood culture is carried out mainly in case of bacteremia, fungemia, or septicemia. Blood culture collection is a sensitive procedure which requires more attentiveness. Nurses work as the first contact person who performs all diagnostic and therapeutic functions. For better diagnosis and error-free results. The nurse should be aware of the blood culture collection procedure, which includes the process from raising a request to receiving a sample at the laboratory receiving counter